Blackface and black representations: a counter-hegemonic history of theater (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
The article investigates the role of the racist practice of blackface in theatre and mass culture, examining its historical occurrences and its continued presence on Brazilian stages. Drawing on the concepts of hegemony and cultural appropriation within Cultural Studies, the research begins with the minstrel show in the United States and moves through Teatro de Revista in Rio de Janeiro, the Teatro Experimental do Negro (TEN) in the 1940s, and the debate following the cancellation of the play A mulher do trem in 2015. Along this trajectory, it shows how the representation of Black people has been at the center of symbolic disputes between hegemonic and counter-hegemonic forces at decisive moments in the country’s history.
Keywords: blackface; black theaters; cultural hegemony; cultural appropriation; whiteness